Single dose of atezolizumab plus chemotherapy in active psoriasis with advanced non-small cell lung cancer. (March 2022) - Wong, Pui Yee; How, Soon Hin; Ismail, Irnani; Hassan, Radhiana
Introduction: Immunotherapy has been recognized as the standard of care in addition to chemotherapy in the treatment of advanced non-small cell lung cancer. Most immunotherapy trials, however, exclude patients with autoimmune disease owing to concerns of disease exacerbation. Case report: We report a case of a patient with advanced non-small cell lung cancer and underlying active psoriasis who experienced a remarkable response, without developing psoriasis flares, following treatment with a single dose of atezolizumab and first-line chemotherapy. Management and outcome: The patient remained asymptomatic 10 months since treatment discontinuation, without disease progression, despite having received only a single dose of atezolizumab and six cycles of chemotherapy. Discussion: Little is known about the optimum duration required to achieve a durable response with immunotherapy. Patients with autoimmune disease are commonly excluded from immunotherapy trials owing to a higher risk of autoimmune disease flares or immune-related adverse events. The remarkable outcome observed in this case offers some insights into the possible durable response with limited doses of immunotherapy and a safer approach for administering immunotherapy in patients with autoimmune disease. Initiating chemotherapy to induce remission in active autoimmune disease prior to administering immunotherapy could potentially be an ideal approach that facilitates the use of immunotherapy in this patient population.